Developing Local Wisdom Based English Learning Materials for History Education students - Syaifudin Latif Darmawan; Fitri Palupi Kusumawati (English Education Study Program, 2023)
This study investigates the transformative impact of integrating locally rooted English language learning materials for history education students at FKIP Universitas Muhammadiyah Metro. Drawing from a collaborative approach involving language educators and history experts, the materials incorporate historical narratives and cultural insights to enhance linguistic proficiency and cultural appreciation. Findings reveal significant improvements in students' language skills, including vocabulary acquisition, grammatical accuracy, and language fluency. Moreover, the materials fostered a deeper connection to cultural heritage, instilling cultural pride and sensitivity. This resonates with the broader discourse on the positive correlation between cultural integration and language education outcomes. The collaborative approach aligns with scholarly recommendations for interdisciplinary collaboration, resulting in materials that are both linguistically rigorous and culturally authentic. The validation process underscores the materials' credibility and effectiveness in bridging language learning and cultural immersion. This study contributes to innovative pedagogical practices that unite linguistic competence with cultural understanding, shaping learners equipped to navigate a globalized world while honoring their cultural heritage.